Pengaruh Pemberian Ekstrak Etanol Bunga Telang terhadap Kadar Il-8 (Interleukin-8) (Studi Eksperimental pada Tikus Putih Jantan Galur Wistar yang dipapar Asap Rokok) - Nurulloh Badar Manggalani; Eni Widayati (Journal of Health, Medical, and Psychological Studies, 2026)
Exposure to cigarette smoke increases oxidative stress and triggers pulmonary inflammation through an increase in Reactive Oxygen Species (ROS), which leads to an increase in interleukin-8 (IL-8). Clitoria ternatea (butterfly pea flower) is rich in anthocyanins, which have antioxidant and anti-inflammatory properties. This experimental study with a post-test only control group design aims to assess the effect of butterfly pea flower ethanol extract on IL-8 levels in male Wistar rats exposed to cigarette smoke. The subjects were divided into normal, negative control, positive control (aspirin 9 mg/kgBW), and two treatment groups with doses of 200 mg/kgBW and 400 mg/kgBW. IL-8 levels were measured using immunological methods. The results showed that IL-8 levels were highest in the negative control group (97.712 ± 0.717 ng/mL) and lowest in the normal group (40.306 ± 0.377 ng/mL). Administration of aspirin and extract doses of 200 mg/kgBW and 400 mg/kgBW significantly reduced IL-8 levels compared to the negative control (p < 0.05). The 400 mg/kgBW dose (42.888 ± 0.350 ng/mL) showed the most effective effect and was comparable to aspirin.